TI_GERICHTE 12.2013.29 vom 3. Oktober 2014 , Appalto - mercede - bollettini a regia - norma SIA - garanzia per difetti - TI Tribunale d'appello (2014)
Appalto - mercede - bollettini a regia - norma SIA - garanzia per difetti